2021
DOI: 10.1002/esp.5272
|View full text |Cite
|
Sign up to set email alerts
|

Experimental insights into the effect of event sequencing and sediment input texture on step‐pool channel evolution

Abstract: We conducted flume experiments in a step‐pool channel with different sediment supply regimes to explore how the sequencing and the grain‐size of sediment pulses affect channel evolution. Our results show that the sequencing of events is not a primary control as the trends in flow characteristics, bedload transport, sediment storage, step evolution, and step frequency were similar in feed phases with different sequencing of sediment pulses. Channel adjustment and step stability in a short timescale (i.e., in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It seems that the relatively high stability of steps in East Creek could be because of the low sediment supply to the channel. The influence of sediment supply on the stability of step-pool morphology has been the focus of several flume experiments (e.g., Hohermuth & Weitbrecht, 2018;Saletti & Hassan, 2020a;Wang et al, 2020Wang et al, , 2021. For example, Hohermuth and Weitbrecht (2018) showed that with the increase in bedload movement step stability deceases.…”
Section: Steps Remain Stable Despite the Mobility Of Individual Keyst...mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the relatively high stability of steps in East Creek could be because of the low sediment supply to the channel. The influence of sediment supply on the stability of step-pool morphology has been the focus of several flume experiments (e.g., Hohermuth & Weitbrecht, 2018;Saletti & Hassan, 2020a;Wang et al, 2020Wang et al, , 2021. For example, Hohermuth and Weitbrecht (2018) showed that with the increase in bedload movement step stability deceases.…”
Section: Steps Remain Stable Despite the Mobility Of Individual Keyst...mentioning
confidence: 99%
“…More recent work (Saletti & Hassan, 2020a, 2020bWang et al, 2020Wang et al, , 2021 showed how additional parameters strongly influence step stability. They identified channel geometry (with areas of local channel narrowing being the more suitable for stable steps) and the magnitude of sediment supply (with a maximum step frequency obtained for values of sediment supply larger than zero but well below transport capacity).…”
Section: Steps Remain Stable Despite the Mobility Of Individual Keyst...mentioning
confidence: 99%